Fluorinated Graphene Oxide; a New Multimodal Material for Biological Applications. (27th August 2013) - Romero‐Aburto, Rebeca; Narayanan, Tharangattu. N.; Nagaoka, Yutaka; Hasumura, Takashi; Mitcham, Trevor M.; Fukuda, Takahiro; Cox, Paris J.; Bouchard, Richard R.; Maekawa, Toru; Kumar, D. Sakthi; Torti, Suzy V.; Mani, Sendurai A.; et al.
<x xml:space="preserve">Abstract</x> Fluorinated graphene oxide (FGO) is reported for the first time as a magnetically responsive drug carrier that can serve both as a magnetic resonance imaging (MRI) and photoacoustic contrast agent, under preclinical settings, and as a type of photothermal therapy. Its hydrophilic nature facilitates biocompatibility. FGO as a broad wavelength absorber, with high charge transfer and strong non‐linear scattering is optimal for NIR laser‐induced hyperthermia. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>